Respuesta :
let be y= world, and joy=x
so we have integral (world)joy^world-1d(joy) = integ(yx^y-1)dx, y is a constant independant of x, so integ(yx^y-1)dx = y . integ(x^y-1)dx
=y .(x^y-1+1 / y-1 +1) + C=(x^y) + C
the answer is joy^world
so we have integral (world)joy^world-1d(joy) = integ(yx^y-1)dx, y is a constant independant of x, so integ(yx^y-1)dx = y . integ(x^y-1)dx
=y .(x^y-1+1 / y-1 +1) + C=(x^y) + C
the answer is joy^world
Answer:
The answer is [tex]joy^{world} + C[/tex]
Step-by-step explanation:
Given the indefinite integral [tex]\int (world)joy^{world-1}d(joy)[/tex]
Let world → a
joy → x
Therefore, the integral becomes [tex]\int ax^{a-1}dx[/tex]
= [tex]a\frac{x^{a-1+1} }{a-1+1} + C[/tex]
= [tex]x^{a} + C[/tex]
Replacing, a → world
x → joy
Hence, [tex]\int (world)joy^{world-1}d(joy)[/tex] = [tex]joy^{world} + C[/tex]